China and Renewables Capitalism in the Green Transition - Lo, Dic; Nyangchak, Niangjijia; Lin, Fanqi (Development and change, 2025)
China stands as both the world's largest emitter of greenhouse gases and the leading producer and user of clean energy technologies. While the country has rapidly expanded its green technology sector, this growth has largely added to, rather than replaced, fossil fuel consumption. This duality presents a complex challenge in assessing China's impact on the global green transition — a challenge which is compounded by ongoing debates about the essence of China's political economy and the relatively early stage of theorizing the broader political and economic implications of the green transition. Rather than debating whether China's system is capitalist or otherwise, this analysis focuses on understanding China through the logic of the pursuit of profits, as well as the country's approach to environmental policy. The transition is often framed in terms of ‘renewables capitalism’, emphasizing either state or market drivers, but this may overlook deeper tensions between the capitalist profit logic and the green transition. By examining these dynamics in a global context, and interrogating the motives behind China's actions, this article aims to shed light both on China's future performance and the extent to which a meaningful green transition is achievable, either within or outside renewables capitalism.